Prevalencia de parásitos gastrointestinales en bovinos del camal de Saquisilí. - Díaz Gallardo, Marco Aurelio (2021)
This investigation addressed the topic of “Prevalence of gastrointestinal parasites in bovine of the Saquisili's slaughterhouse", these parasites are the main limitation in the development of animals and even originate infections for humans. The objective of the investigation is to determine the prevalence of parasitic species in the gastrointestinal tract of bovine, with the purpose of achieve an effective sanitary management of the herds and higher productivity. The study was realice in the technological Saquisili´s slaughterhouse, were sample 100 bovine without distinction of sex or their place of origin, because was research relation between sex and origin. Obtaining the following results from the 100 sampled animals, a prevalence of 46% of parasitized animals, the genus of gastrointestinal parasite with the highest prevalence was Nematodirus with 51.6%, in relation to the sex factor it was obtained of 48 females the 39, 58% were positive and of 52 males 51, 92% were positive. Regarding the origin factor, is evident that the place with the highest prevalence of gastrointestinal parasites was Cochapamba, with 28 animals, obtained 39.1% of animals were positive for the presence of parasites.